The U.S. Role and Policies in International Peacekeeping Operations and Peace Building: Potential Engagement with the South Caucasus (International Journal of Contemporary Security Studies, 2024)
The paper is discussing the potential US peace-keeping engagement with the South Caucasus after the Third Nagorno-Karabakh war. Based on the case-study of the Third Nagorno-Karabakh war, followed by ethnic cleaning of the Armenians of Nagorno-Karabakh and continuous Azerbaijani aggression towards the sovereign territory of the Republic of Armenia, the paper analyzes the US interests and draws potential scenarios for US peacekeeping engagement in Armenia-Azerbaijani conflict. It draws five potential scenarios, which are: direct military engagement, support to a UN (or other international organization, for instance, OSCE) mission, support to the EU mission in Armenia, NATO engagement, distancing, and argues that the most realistic model is the US direct diplomatic engagement with major support to the EU/EU countries’ efforts, including military, in Armenia.
Keywords: Armenia; United States; Azerbaijan; Peacekeeping; South Caucasus; Peacebuilding